New Zealand : Statistical Annex. (IMF Staff Country Reports; Country Report, 2000)
This report provides details of the IMF's projections and estimates on New Zealand's gross domestic product by sector; selected indicators of economic activity; expenditure on GDP; price and wages; labor market developments; balance of payments; financial survey; services and income; interest rates and yields; gross official international reserves; changes in volumes and unit values of exports and imports during 1995-2000; summary of central government budget and balance sheet during 1994/95-2001/02; central government tax revenue and expenditure during 1992/93-1999/00, and so on.